2006
DOI: 10.1111/j.2006.0906-7590.04575.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection as a mechanism of resource partitioning in two cryptic bat species Pipistrellus pipistrellus and Pipistrellus pygmaeus

Abstract: Ecomorphological studies of bat communities often reveal the spatial and temporal coexistence of morphologically similar species, leading to suggestions that these communities are structured by non‐deterministic processes. However, the diversification of echolocation call structure in bats allows for considerable morphological similarity while still permitting niche differentiation based on specialisation for prey type and habitat structure. The recent separation of a common Palaearctic bat, the pipistrelle, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 55 publications
9
81
2
3
Order By: Relevance
“…In Switzerland, stenotopic P. pygmaeus uses a much narrower habitat niche than eurytopic P. pipistrellus but completely overlaps with the niche of the latter (Sattler et al 2007). On the contrary, a principal component analysis, performed by Nichols and Racey (2006) on the proportion of time spent in each habitat, showed a distinct clustering of radiotracked individuals of the two species, with no overlap, providing clear evidence for habitat partitioning.…”
Section: Niche Overlap and Resource Partitioningmentioning
confidence: 90%
See 2 more Smart Citations
“…In Switzerland, stenotopic P. pygmaeus uses a much narrower habitat niche than eurytopic P. pipistrellus but completely overlaps with the niche of the latter (Sattler et al 2007). On the contrary, a principal component analysis, performed by Nichols and Racey (2006) on the proportion of time spent in each habitat, showed a distinct clustering of radiotracked individuals of the two species, with no overlap, providing clear evidence for habitat partitioning.…”
Section: Niche Overlap and Resource Partitioningmentioning
confidence: 90%
“…Co-occurring P. pipistrellus and P. pygmaeus may reveal partial-although subtle-separation of habitat niches (Nichols and Racey 2006). In south-western England, P. pygmaeus is more strongly associated with water bodies and riparian habitats in general, while P. pipistrellus uses a much broader habitat niche, also including arable land and villages (Vaughan et al 1997a;Davidson-Watts et al 2006).…”
Section: General Habitat Preferences Of Bats In the Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Nicholls and Racey 2006), Nathusius' pipistrelle, Pipistrellus nathusii (Flaquer et al 2009), and other Pipistrellus spp. (Scott et al 2010), Schreiber's bat Miniopterus schreibersii (Serra-Cobo et al 2000) and noctules, Nyctalus spp.…”
Section: Bodies Of Water As a Foraging Habitatmentioning
confidence: 99%
“…Vaughan et al 1997 522 We suggest that in spring P. kuhlii is associated with 523 small ponds, despite their lower insect abundance, to avoid 524 competition with T. teniotis and H. bodenheimeri for 525 drinking or foraging space above large ponds and with 526 P. rueppelli for foraging space above medium ponds. 527 Similarly, sympatric cryptic Pipistrellus species in the UK 528 partition their foraging habitat to the extent that P. pipi-529 strellus actively avoids riparian habitats, which are pre-530 ferred by P. pygmaeus, despite their greater insect resource 531 value (Nicholls and Racey 2006). 532 Although the diversity of Dipterans increases with pond 533 area and hydroperiod (Bazzanti et al 2006), some species 534 may be found exclusively in lower volume, shorter-lived…”
mentioning
confidence: 99%